The logic of data-sense: thinking through Learning Personalisation. Issue 5 (3rd September 2017) - Thompson, Greg; Cook, Ian
ABSTRACT: Big Data and Learning Analytics' promise to revolutionise educational institutions, endeavours, and actions through more and better data is now compelling. Multiple, and continually updating, data sets produce a new sense of 'personalised learning'. A crucial attribute of the datafication, and subsequent profiling, of learner behaviour and engagement is the continual modification of the learning environment to induce greater levels of investment on the parts of each learner. The assumption is that more and better data, gathered faster and fed into ever-updating algorithms, provide more complete tools to understand, and therefore improve, learning experiences through adaptive personalisation. The argument in this paper is that Learning Personalisation names a new logistics of investment as the common 'sense' of the school, in which disciplinary education is 'both disappearing and giving way to frightful continual training, to continual monitoring'.